2012
DOI: 10.1111/j.1365-2133.2012.11132.x
|View full text |Cite
|
Sign up to set email alerts
|

The association of vitamin D receptor gene polymorphisms and serum 25-hydroxyvitamin D levels with generalized vitiligo

Abstract: Our findings suggest that these VDR polymorphisms are associated with 25(OH)D levels and that there exists a genetic predisposition for vitiligo in the Chinese population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
84
4
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(101 citation statements)
references
References 37 publications
11
84
4
2
Order By: Relevance
“…However, studies on relationships between Pb and serum 25(OH)D are few; most were done more than two decades ago when BLL were much higher ($29 mg/dl) and have yielded inconsistent results (17)(18)(19)(20)(21) . (22,23) . Hence, with the improvement of the environment and prevention measures for Pb exposure, a new relationship between vitamin D and BLL that is lower than in the past should be established.…”
Section: The Concentration Of 25-hydroxyvitamin D (25(oh)d)mentioning
confidence: 99%
“…However, studies on relationships between Pb and serum 25(OH)D are few; most were done more than two decades ago when BLL were much higher ($29 mg/dl) and have yielded inconsistent results (17)(18)(19)(20)(21) . (22,23) . Hence, with the improvement of the environment and prevention measures for Pb exposure, a new relationship between vitamin D and BLL that is lower than in the past should be established.…”
Section: The Concentration Of 25-hydroxyvitamin D (25(oh)d)mentioning
confidence: 99%
“…[12][13][14][15][16][17][18][19][20] There was no significant decrease in vitamin D levels in patients with associated autoimmune comorbidity in our study. Similar results have been found by Khurrum et al, Saleh et al as well as Beheshti et al 7,18,19 All other studies had found a significant decrease in vitamin D levels in patients having comorbid autoimmune conditions.…”
Section: Discussionmentioning
confidence: 89%
“…Similar results were obtained in a study by Finamor et al as well as Takczi et al 9,11 However the majority of patients in other studies had a mean age below 35. [6][7][8][12][13][14][15][16][17][18][19][20] This may reflect certain social attitudes towards the disease i.e. hesitancy to consult local physicians regarding vitiligo, or presenting to a tertiary center only after prolonged native treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Vitiligo and autoimmunity may be influenced by vitamin D and a recent Chinese study documents low levels of 25-hydroxy vitamin D in vitiligo 42 . Treatment with calcipotriol is a reminder of the role of vitamin D precursors 1,25(OH) 2 D, which even 500 million years ago protected primitive cellular organisms from environmental hazards, including ionizing and UV-irradiation, microbial infections and oxidative stress 43 .…”
Section: Lerner's Theory Of Self-destructionmentioning
confidence: 99%